الحماية القانونية للشيك في التشريع الجزائر - لغريب, مسعودة (جامعة الوادي University of Eloued, 2017)
لدراسة هذا الموضوع قسمناه إلى فصلين وكل فصل إلى مبحثين وكل مبحث إلى مطلبين. حيث تناولنا في الفصل لأول الحماية ا لمدنية للشيك في التشريع الجزائري من خلال مبحثين هما المبحث الأول مفهوم الشيك حيث سنتطرق في المطلب الأول المقصود بالشيك والشروط الموضوعية والشكلية للشيك في مطلب ثاني. أما المبحث الثاني فكان بعنوان أنواع الشيك وتمييزه عن غيره من الأوراق التجارية الأخرى وتم تقسيمه إلى مطلبين هما على التوالي المطلب الأول أنواع الشيك والمطلب الثاني تمييز الشيك عن غيره من الأوراق التجارية. أما بالنسبة للفصل الثاني وهو تحت عنوان الحماية الجنائية للشيك وفيه المبحث الأول جريمة إصدار شيك دون رصيد، وقسمناه إلى المطلب الأول جريمة إصدار شيك دون رصيد وإجراءات المتابعة في مطلب ثاني. أما المبحث الثاني جريمة التزوير والتقليد في الشيك وفيه مطلب أول أركان جريمة التزوير والتقليد في الشيك والمطلب الثاني إجراءات المتابعة والجزء المقرر لها. two sections and each subject to two requirements. Where ewe discussed in the chapter the first civil protection of the check in the Algerian legislation through two sections, the first topic is the concept of the check where we will address the first requirement intended check and the substantive and formality of the check in the second demand. The second section was entitled Types of check and distingue shitfromother commercial papers and wasdividedint two requirements, respectively, the first requirement types of check and the second requirement to distinguish the check from other commercial papers. As for the second chapter, which under the heading of criminal protection of the check, in which the first section is the crime of issuing a check without a balance, wedivideditinto the first demand, the crime of issuing a check without balance and the follow-up procedure in the second demand. The second section is the crime of fraud and counterfeiting in the check, In the check and the second application the follow-up procedures and the planned
قانون أعمال
Keywords: شيك – إصدار–دونرصيد–تزوير- جريمة; check - issuance - without credit - fraud – crime